Reactive Strength Index as a Predictor of Jump Height and Agility in Basketball Athletes - Joseph Kurian; Aswin Prasad; Mary Mohare; Nupur Gandhe Harshe; Arun T Prasanna; U.V. Sankar (Recent Trends in Sports, 2024)
This study examines the relationship between the Reactive Strength Index (RSI) and specific performance metrics, namely jump height and agility, in youth basketball players. The RSI, a measure derived from drop jump testing, provides insight into an athlete’s explosive strength and reactive capabilities—essential qualities for success in basketball, where quick directional changes and reactive power are integral to performance. A cohort of forty youth athletes, comprising 20 males and 20 females, participated in the study and underwent both baseline (pre-test) and follow-up (post-test) assessments. Key performance metrics included RSI values derived from drop jumps, Vertical Jump height, and T-test agility scores. Comparative analyses were also conducted by gender and age bracket to investigate demographic influences on RSI and other performance indicators. Results revealed a significant positive correlation between RSI and agility scores, indicating that athletes with higher RSI values tend to perform better in agility tasks. This relationship underscores the value of RSI as a predictive indicator for on-court agility and performance. Additionally, demographic analysis suggested that RSI scores were generally higher in male participants and in older age groups, hinting at the impact of maturity and physical development on reactive strength in youth athletes. These findings advocate for the practical use of RSI as an assessment and training tool in youth basketball settings. By integrating RSI testing, coaches can better identify strengths and areas needing development, creating tailored strength and conditioning programs that enhance on-court performance and mitigate injury risks. Overall, RSI proves to be a valuable tool for assessing and optimizing athletic potential in basketball, offering coaches a reliable metric to inform training and performance development.
Keywords: Performance Metrics; Reactive Strength Index; agility; basketball; youth athletes